Cerebral schistosomiasis in a patient travelling from São Tomé and Príncipe - Armindo, Rui Duarte; Costa, Sónia; Almeida, Vânia; Barroso, Cândida (My University, 2020)
Aiming to raise awareness for the possibility of schistosomal involvement of the central nervous system in travellers returning from endemic areas and/or immigrants to nonendemic areas, the authors report a case of neuroschistosomi asis in a Portuguese patient coming from the Republic of São Tomé and Príncipe with good clinical outcome following praziquantel therapy. This is the first case of neuroschistosomiasis associated with São Tomé and Príncipe reported in literature and further studies are needed to confirm which species of this parasite are endemic of that region. We conclude that early diagnosis is key to reduce clinical severity and therefore validation of new diagnostic techniques and establishment of consensual treatment guidelines would be important.